Kajian Intertekstual dalam Webtoon "Nusantara Droid War" - Rizki Nufiarni; M. Andhy Nurmansyah; Fredy Nugroho Setiawan (Haluan Sastra Budaya, 2024)
LINE Webtoon is a popular digital comic platform in Indonesia that accommodates the work of local comic artists, one of which is a comic titled Nusantara Droid War (NDW). The comic carries a glocal spirit by raising the diversity of Indonesian culture through the depiction of droid characters and present them with a typical Japanese-style shonen manga plot. The intertwining of various folklore and culture of the archipelago with the popular narrative of shnen manga shows the existence of intertextuality. Therefore, this study was structured to examine the intertextuality of NDW in webtoon characters and narratives by applying Roland Barthes' postulates regarding the Five Codes of semiotic elements in texts to interpret intertextuality that is embodied in a series of lexia in NDW. The results of this study indicate that the Nusantara Droid War (NDW) text is a readerly text, although it is not absolute. The intertextuality depicted through the Five Codes: hermeneutic, proairetic, semantic, symbolic, and cultural/referential is dominated by texts originating from the Mahabharata story, legends from Indonesian folklore, and Japanese shounen anime or manga. In this case, referential code contributes the most in lexia, which also indicates that cultural texts play an important role in NDW text building. The discourse of intertextuality leads the NDW reading process to reject the 'artificial thing', namely the market logic that positions popularity and ownership of capital as the main goal in the world of entertainment, including the battle between droids in NDW.